A Study of Learning Achievement on Conserving Hometown Unit, Problem Solving Ability and Analytical Thinking Ability of Grade 6 Students Using Problems Based Learning - Silakate, Wiphawan; Naowanondha, Adisorn (Ratchaphruek Journal, 2022)
The study was aimed to compare the students’ learning achievement, the problem solving ability skill, and the analytical thinking ability of grade 6 students by using Problem Based Learning technique. The purposes of this research were to: 1) Compare learning achievement before and after using problems based learning, and after with 70% criteria; 2) Compare problem solving ability before and after using problems based learning, and after using with 70% criteria; and 3) Compare analytical thinking ability before and after using problems based learning, and after using with 70% criteria.The sample was 17 Bantachan students from grade 6, first semester of 2018 academic year by cluster random sampling. The data were collected by lesson plans, a learning achievement test, a problems solving ability test, and an analytical thinking ability test. The data were analyzed by percentage, mean, standard deviation, and t-test. The results of the study were found that: After using Problem Based Learning technique, All the three aspects; Learning achievement, problems solving ability, and analytical thinking ability, the students’ learning scores were higher significantly than before at the .05 level, and were higher significantly than 70% criteria at the .05 level.